The unique Kuri cattle of the Lake Chad Basin - Mpofu, N.; Rege, J.E.O. (International Livestock Research Institute, 2002)
The Kuri cattle breed is found on the shores and islands of Lake Chad. Its main habitat is in southern Chad and north-eastern Nigeria but the breed is also found in northern Cameroon, in Niger and, to a limited extent, in the Central African Republic. The Kuri are also known as the Baharie, Bare, Borrie, Boudouma, Dongolé, Koubouri, Buduma or White Lake Chad. The importance of the Kuri lies not only in its unique physical characteristics but also in its meat and milk production potentials. The breed is so acclimatised to the environs of Lake Chad that it is unable to survive elsewhere. This unique African breed is being threatened by extinction.